If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 39(x + 4) = 5x + 16 Reorder the terms: 39(4 + x) = 5x + 16 (4 * 39 + x * 39) = 5x + 16 (156 + 39x) = 5x + 16 Reorder the terms: 156 + 39x = 16 + 5x Solving 156 + 39x = 16 + 5x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-5x' to each side of the equation. 156 + 39x + -5x = 16 + 5x + -5x Combine like terms: 39x + -5x = 34x 156 + 34x = 16 + 5x + -5x Combine like terms: 5x + -5x = 0 156 + 34x = 16 + 0 156 + 34x = 16 Add '-156' to each side of the equation. 156 + -156 + 34x = 16 + -156 Combine like terms: 156 + -156 = 0 0 + 34x = 16 + -156 34x = 16 + -156 Combine like terms: 16 + -156 = -140 34x = -140 Divide each side by '34'. x = -4.117647059 Simplifying x = -4.117647059
| 5-2y=3x | | 118.8-7.7x=3.3+39.6 | | 8=-5y-2 | | 2/3-7= | | -5n+x=78 | | 8(2n-3)=(2n+8)+3 | | 5x+5x+4+8=7x+4+2x | | -3(t+4)=3 | | 3(2-z)*0.2=z | | (3x)+4=-11 | | 11(2+8x)-10(10-11x)=912 | | -2(x-18)=(-x/2+3)(-3) | | 12=4n-10 | | x^3=216 | | -5=-x+3 | | 6x+2+3x+17=10 | | 3n+6n=3-9 | | .6a-.75b=c | | 7(-2x+6)=126 | | 5a^2+20a+3=0 | | -3q+4=q | | 3(3x+4)+3(3x+4)=18x+30 | | 7x+4+4x+9=10x+3 | | 3(x+7)-3(x+2)=36 | | 6y^2+9y=11y-4 | | 4v^2-28v+49=0 | | 3(x+7)-3(x+2)=-36 | | 6+8(x-9)=9-3(x-9) | | z-5=7z-9-z | | x-6=7x | | x=5my-7b | | 8x+3-7x=11 |